2015
DOI: 10.1111/acem.12674
|View full text |Cite
|
Sign up to set email alerts
|

The Use of a Video Laryngoscope by Emergency Medicine Residents Is Associated With a Reduction in Esophageal Intubations in the Emergency Department

Abstract: Objectives: The purpose of this investigation was to compare the incidence of esophageal intubations (EIs) when emergency medicine (EM) residents used a direct laryngoscope (DL) versus a video laryngoscope (VL) for intubation attempts in the emergency department (ED). Methods:Prospectively collected continuous quality improvement data on tracheal intubations performed by EM residents in an academic ED over a 6-year period were retrospectively analyzed. Following each intubation, EM residents completed a data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 29 publications
2
55
1
Order By: Relevance
“…Video laryngoscopy use during emergency airway management is increasing over time, while DL use is decreasing, particularly when a difficult airway is anticipated . Multiple ED observational studies support this evolution in clinical practice having shown that VL improves glottic exposure and first‐attempt success and reduces the incidence of peri‐intubation adverse events . A single‐center registry from an academic ED reported that CMAC‐facilitated intubations resulted in significantly higher first‐attempt success compared with DL but did not specifically compared VL to A‐DL .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Video laryngoscopy use during emergency airway management is increasing over time, while DL use is decreasing, particularly when a difficult airway is anticipated . Multiple ED observational studies support this evolution in clinical practice having shown that VL improves glottic exposure and first‐attempt success and reduces the incidence of peri‐intubation adverse events . A single‐center registry from an academic ED reported that CMAC‐facilitated intubations resulted in significantly higher first‐attempt success compared with DL but did not specifically compared VL to A‐DL .…”
Section: Discussionmentioning
confidence: 99%
“…Direct laryngoscopy (DL) has been the historical standard for emergency airway management; however, video laryngoscopy (VL) has been shown to improve glottic view and first‐attempt success compared to DL in emergency department (ED) patients and its use in preference to DL has steadily increased . Maximizing first‐attempt success improves patient safety, reduces peri‐intubation adverse events, and the available evidence supports the use of VL as the first‐line device for emergency airway management . Glottic view is superior with VL because it effectively places the operator's eye at the leading edge of the blade, allowing the clinician to see around the base of the tongue and overcoming the challenge of creating a direct line of sight.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For emergency airways, most observational and retrospective studies indicate that C-MAC device performs better than direct laryngoscope, especially for patients with a Cormack–Lehane grade 3 or 4 4148,50,51. After a failed first intubation attempt in the emergency department, C-MAC device is more successful at second attempt than the direct laryngoscope 51.…”
Section: Commentsmentioning
confidence: 99%
“…Several observational and retrospective studies from emergency department, prehospital and ICU patients showed that a V-MAC or C-MAC device, compared with a direct laryngoscope, was associated with a significantly better visualization of the larynx and a higher proportion of successful intubations, especially for patients with predicted difficult intubations 4347. Furthermore, the use of C-MAC videolaryngoscope during emergency intubation was associated with significantly fewer esophageal intubations compared with direct laryngoscopy 43,48,49…”
Section: Introductionmentioning
confidence: 99%